Developing a service user informed intervention to improve participation and ability to perform daily activities in primary Sjögren's syndrome: a mixed-methods study protocol. Issue 8 (21st August 2014) - Hackett, Katie L; Newton, Julia L; Deane, Katherine H O; Rapley, Tim; Deary, Vincent; Kolehmainen, Niina; Lendrem, Dennis; Ng, Wan-Fai
Abstract : Introduction: A significant proportion of patients with primary Sjögren's syndrome (PSS) is functionally impaired and experience difficulties participating in various aspects of everyday life. There is currently no evidence of efficacy for non-pharmacological interventions aimed specifically at supporting the patients with PSS to improve their participation and ability to perform daily activities. This paper describes a research protocol for a mixed-methods study to develop an intervention to improve these outcomes. The protocol follows the Medical Research Council framework for complex interventions. Methods and analysis: We will use group concept mapping with the patients, adults who live with them and healthcare professionals to identify factors which prevent people with PSS from participating in daily life and performing daily activities. The factors will be prioritised by participants for importance and feasibility and will inform an intervention to be delivered within a National Health Service (NHS) setting. Evidence-based intervention techniques will be identified for the prioritised factors and combined into a deliverable intervention package. Key stakeholders will comment on the intervention content and mode of delivery through focus groups, and the data will be used to refine the intervention. The acceptability and feasibility of the refined intervention will be evaluated in a future study. Ethics and dissemination: The study has been approved by an NHS Research Ethics Committee, REC Reference: 13/NI/0190. The findings of this study will be disseminated in peer-reviewed journals and through presentation at national and international conferences. Trial registration number: UKCRN Study ID: 15939.